The Main Refrigeration Compressor di KM. Sabuk Nusantara 37 pada PT. Pelni - Erita Erita; Syefli Ewimia Darza; Ade Putra Kurniawan; Nofrizal Nofrizal (Sekolah Tinggi Maritim Yogyakarta, 2021)
With the development of technology and the progress of the times at this time it turns out that the cooling system provides many benefits for humans that we may unconsciously feel so far. cooling systems are generally widely used for industrial and commercial purposes. At this time, Refrigeration is a tool whose role in human life today is arguably quite large. Refrigeration is used to store food ingredients, vegetables and even fruits. The research was conducted on problems or damages that occurred in refrigeration on the KM Belt Nusantara 37 ship at PT Pelni. The type of research used in this thesis is descriptive research, using a qualitative approach. Data analysis was carried out using descriptive methods, namely methods that were carried out by first collecting existing data then classified, then interpreted so as to provide solutions to problems. The 8 most common problems in the refigeration system on KM ships. Belt Nusantara 37 is a compressor that runs but stops suddenly, Compressors start and stop too often, Compressors run continuously, Unusual noise on the compressor, High Discharge Temperature, Frost on the Evaporator, Decreased cooling ability, Less oil in the compressor .